Thermosensitive response of a functionally graded cylinder with fractional order derivative - Lamba, Navneet Kumar (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with thermal behaviour analysis of an axisymmetric functionally graded thermosensitive hollow cylinder. The system of coordinates are expressed in cylindrical-polar form. The heat conduction equation is of time-fractional order, subjected to the effect of internal heat generation.
Keywords: time fractional; thick hollow cylinder; thermal stresses; internal heat generation; FGMs; thermosenstive